2014
DOI: 10.1002/eat.22328
|View full text |Cite
|
Sign up to set email alerts
|

How do parents of adolescent patients with anorexia nervosa interact with their child at mealtimes? A study of parental strategies used in the family meal session of family‐based treatment

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available. Copies of full items can be used for personal research or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
(37 reference statements)
0
20
0
1
Order By: Relevance
“…In the current study, we developed a novel 3 session intervention that is conceptually and procedurally compatible with FBT called Intensive Parental Coaching (IPC). IPC provides in vivo coaching that specifically targets parental self-efficacy related to re-feeding strategies (detailed below) so that their child starts to regain weight faster (Darcy et al, 2013; Doyle et al, 2010; White et al, 2015). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we developed a novel 3 session intervention that is conceptually and procedurally compatible with FBT called Intensive Parental Coaching (IPC). IPC provides in vivo coaching that specifically targets parental self-efficacy related to re-feeding strategies (detailed below) so that their child starts to regain weight faster (Darcy et al, 2013; Doyle et al, 2010; White et al, 2015). …”
mentioning
confidence: 99%
“…Our second aim was to gather preliminary data on the treatment effect of IPC in the context of FBT for early poor responders. In addition, previous studies suggest that improving parental self-efficacy is a possible mechanism leading to successful re-feeding efforts by parents and weight gain in their child with AN (Byrne, Accurso, Arnow, Lock, & Le Grange, 2015; White et al, 2015). We therefore also examined changes in parental self-efficacy as a treatment target in FBT and FBT+IPC.…”
mentioning
confidence: 99%
“…The Pubmed search resulted in 192 titles for inspection and 7 abstracts for inspection of which 5 were not trials of treatment setting [28][29][30][31][32] and one was a review [33] and one new trial [34] was identified. The CCRCT Issue 6 of 12, June 2014 (n = 797723) search resulted in 20 titles for inspection of which two were duplicates and one new trial [29] was identified ( Figure 1).…”
Section: Results Of Searchmentioning
confidence: 99%
“…A diferencia de estudios previos en los que la CTF se ha implementado, como parte del protocolo de la TBF, exclusivamente en familias de pacientes adolescentes (Godfrey et al, 2015;Fitzpatrick et al, 2015;White et al, 2015;Wallis et al, 2016), el presente estudio incluyó a pacientes sin restricción de edad. Esto en el entendido de que los factores de interacción familiar pueden ejercer un rol mantenedor de los síntomas a cualquier edad, y especialmente al considerar que la enfermedad impone comportamientos regresivos que retardan la construcción de la autonomía y la independencia en estos pacientes.…”
Section: Características Del Menú Llevado a La Sesiónunclassified